Restoran Bisnis Berbasis Standar Kompetensi - Endang Darwin Durachim; Faizal Hamzah (Jurnal Pariwisata, 2017)
Restaurant  Business base on competency is something important point to be presented on the activities of management  Hotel or  Restaurant, the reason is those thing  will up-grade  the Restaurant Business much better then  before. Especially on the situation and condition of the business  right now the competition  getting  so tight. So causing  of those case we have to provide as well as possible , how to make the Competency Standard Attitudes, Skills and Knowledge are being  presented  on  Restaurant Business. Actually the Competency Standard  have three dominant factors indeed such as:  All of dominant factors must be done in perfect condition  or excellent  Presentation , why  the Competency Standard  must be done in perfect condition ? because if the staff who In-Charge in the operation of the restaurant business, they are doing something Excellence Attitudes, Excellence Skills and Excellence Knowledge, so the whole of activities will be running well according to the necessarily of the restaurant business operation . In order to obtained  an optimal result in the operation of the Restaurant  Business is excellence of the presentation of the competency standard was carry out  by Management and Staff. The basic purpose to obtained an optimal result was  presented  by  Competency Standard , it will make all the guests / customers  are satisfied, and  automatically  the productiveness  / benefit or profit  will come over directly to the management.  Competency Standard is a statement of three interrelated components of Skills, Knowledge,and attitudes needed to carry out a particular tasks effectively in Industry. These are benchmarks made by Industry that are to be used to establish level of effective performance . They  provide a framework to suit the needs of all  the stockholder (Industry, Government , Training Provider, Trainees), regardless of location size.  Key Factors:  Restaurant Business Base on Competency , Socialization and Implementation of Competency Standard, Hierarchy of positions of Competency Standard in Tourism & Hospitality Industry,Realization  powerful of strategy restaurant business base on competency standard .